2019
DOI: 10.21608/jpp.2019.36264
|View full text |Cite
|
Sign up to set email alerts
|

Cauliflower Growth, Yield and Quality Response to Nitrogen Fertilization and Micronutrients Foliar Application in Newly Reclaimed Areas

Abstract: Two field experiments were carried out during 2017/2018 and 2018/2019 seasons, at the Experimental Farm, Faculty of Agriculture, New Valley University, New Valley governorate, Egypt, to study the effect of nitrogen levels (30, 45 and 60 kg/fed.) and micronutrients foliar application: control (B 0 + Mo 0), boron at 100 ppm (B 100), molybdenum at 50 ppm (Mo 50) and combined boron and molybdenum (B 100 + Mo 50) on cauliflower vegetative growth, yield, and quality parameters in the recently reclaimed areas, especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Nitrogen fertilization has an important role in increasing the yield and growth parameters of cauliflower, as in other Cruciferous vegetable species. Similar to our findings, earlier studies have also reported that nitrogen fertilization significantly increased the plant growth and chlorophyll content in cauliflower [17,[30][31][32] since nitrogen plays important roles in the meristematic development, chlorophyll formation, and photosynthesis [30]. On the other hand, increasing N doses lowered the vitamin C content of cauliflower heads.…”
Section: Discussionsupporting
confidence: 92%
“…Nitrogen fertilization has an important role in increasing the yield and growth parameters of cauliflower, as in other Cruciferous vegetable species. Similar to our findings, earlier studies have also reported that nitrogen fertilization significantly increased the plant growth and chlorophyll content in cauliflower [17,[30][31][32] since nitrogen plays important roles in the meristematic development, chlorophyll formation, and photosynthesis [30]. On the other hand, increasing N doses lowered the vitamin C content of cauliflower heads.…”
Section: Discussionsupporting
confidence: 92%
“…Results in this research clear that increasing nitrogen micro carbon increased al aforementioned parameters this may be due to increase photosynthetic pigments (Ali et al, 2019) protein and nucleic acids then increase physiological processes and metabolism this lead to increase leaves area and large vegetative growth (as shown in Table 2) that improve carbohydrate synthesis to accumulate extra dry matter in curds (reproductive tissues) this reflect to curds growth and yield (Laghari et al, 2016) and improve curds quality. These results are conformity with those obtained by Hussain et al (2012), Metwaly (2016) on broccoli, Abdrabbo et al (2019) on sweet fennel and Ali et al (2019).…”
Section: Discussionmentioning
confidence: 75%
“…The highest head weight (888.00 g) and maximum yield of head (25.97 t/ha) were obtained during 1 st year respectively (Table 9). [20].…”
Section: Case 3 Studies On Promising Influence Ofmentioning
confidence: 99%